Evaluasi Debit Pada Saluran Irigasi Namu Sira-Sira Berdasarkan Pengukuran Kecepatan Dan Kedalaman Air - Kristina Marbun; Lidia Intan Pratiwi Zai; Joshua Rizky Fransisco Sianturi; Yuni Yolanda Sitepu (Fakultas Teknik Universitas Hamzanwadi, 2026)
Irrigation is a crucial component in supporting agricultural productivity as it plays a role in the provision and distribution of water to agricultural land. The availability of an appropriate flow rate significantly determines the effectiveness of the irrigation system in meeting the water needs of crops. Evaluation of the flow rate in irrigation channels is necessary to determine the channel's ability to optimally drain water. This study aims to evaluate the flow rate in the Namu Sira-Sira Irrigation Channel based on measurements of flow velocity and water depth using a simple float method in the form of a bottle. Measurements are made by determining the water flow velocity through the bottle's travel time at a certain distance, then measuring the channel's cross-sectional dimensions to obtain the wetted area. The flow rate is calculated using the discharge equation as the result of multiplying the wetted area by the average flow rate. The results of this study are expected to provide an overview of the flow rate conditions in the Namu Sira-Sira Irrigation Channel and become evaluation material in managing and improving the efficiency of the irrigation system. The simple measurement method used is also expected to be a practical alternative in measuring flow discharge in irrigation channels in the field